The German Construction Industry: Production and Employment 2007/2008 - Martin Gornig (Weekly Report, 2008)
In 2006, after years of stagnating and even significantly declining production, the construction industry finally experienced a year of strong growth (Table 1). In nominal terms, the industry expanded by 7% in 2006. After allowing for price increases, there was real growth of almost 5%, much higher than expected. Admittedly, one cause of this expansion was the effect of a VAT increase announced for 1 January 2007. A large number of both public and private investors brought projects forward to 2006 to avoid the increased VAT charges. Yet at the beginning of 2007, undiminished high construction production could be observed and there was no sign of the expected backwash effects. In the course of the year, however, the growth rate in construction slowed considerably. There was a steep rise in construction prices at the beginning of 2007. Here, the large increase in VAT as of 1 January 2007 must be taken into account. But even without the effect of higher VAT, the price increase over the previous year amounts to around four percent. This is partly due to higher construction costs. On the other hand, we can assume that companies also experienced an improvement in their earnings. Towards the end of 2007, prices began to stabilize. Nevertheless, the average real growth of construction volume for 2007 was only just under 2%. In 2008, continued moderate growth is expected for real construction volume. The annual average growth rate should be 1%. In the new Länder the growth rate should be lower than in the old Länder.
Keywords: L74; O11; 330; Housing demand; Construction industry; Estimates 2008